The Directions of Settlement Development on Land Availability in Ternate City - Eva Purnamasari; Yudi Antomi (Journal of Applied Geospatial Information, 2023)
The development of settlements experienced by the City of Ternate has caused quite serious problems, considering that the City of Ternate is an island city dominated by mountainous land, land development for settlements is limited to coastal lands. The purpose of this study is to analyze the direction of settlement development toward the availability of land in the City of Ternate. The method used in this research is the overlay method and uses a qualitative descriptive research type using secondary data in the form of a Map of Disaster Prone Areas from the Ministry of Energy and Mineral Resources. From the results of the overlapping process between settlements in 2010 and 2020, the direction of settlement development in the City of Ternate is to the south and east which are pointing upwards on the slopes of Mount Gamalama. Judging from the Disaster Prone Areas (KRB) map obtained from the Ministry of Energy and Mineral Resources, the direction of settlement development that has occurred in Ternate City is that KRB I is an area that is located along or near the river valley and the lower reaches of the river which originates at the peak area. The availability of land in the City of Ternate which allows for the construction of a settlement is in the south and east. However, the southern and eastern parts of Ternate City are dense enough so that the dominant development is directed upwards. This upward development needs to consider the slope of the slope considering that Ternate City is a volcanic island.